Sita, Snake-Queen of Speed - Ewart, Franzeska G.; Bate, Helen (London : Frances Lincoln Children's Books, 2008)
Yosser and Kylie decide that Kylie's father's prize ferret--Thunderball Silver the Third--is their ticket to earning enough money to experience best ride at Thrill City, but in order to collect they must find it before the Grand Ferret Championships.
Kirkus Review
6.0
3-6
3-6
Keywords: Amusement rides -- Juvenile fiction; Ferret -- Juvenile fiction; Money-making projects for children -- Juvenile fiction; Amusement rides -- Fiction; Ferret -- Fiction; Moneymaking projects -- Fiction; Amusement rides -- Fiction; Ferrets -- Fiction; Money-making projects for children -- Fiction